CORRELATION ANALYSIS AND CROSS-PRINT BETWEEN THE SEVERAL CHARACTERS OF LOCAL GOGO RICE CULTIVARS (Oryza sativa L.) - Sakka Samudin; Maemunah Maemunah; Usman Made; Andi Ete; Mustakim Mustakim; Saharil Darmin (Universitas Tadulako, 2022)
The relationship between several characters of yields is very important for developing effective selection criteria. The total correlation between the result character and the result component may be misleading as a result of its relationship with other characters. Separating the total correlation into direct and indirect effects provides a more significant explanation of the cause of the relationship between dependent variables such as yield and independent variables such as yield components. This study aims to determine several traits that can be used to make selections indirectly and directly to increase the yield of upland rice. This research has been carried out on agricultural land in the village of Tamarenja (Kalama), Sindue District, Donggala Regency. Starting from August to December 2019, using a Randomized Block Design (RBD) with seven genotypic cultivars and three groups of cultivars so that there were twenty one experimental plots. The results showed that the number of leaves, leaf length, number of tillers, number of productive tillers, flowering age, thickness of seeds and weight of 1000 grains had a positive and significant correlation to yield. Flowering age, 1000 grain weight, and number of tillers are some of the characteristics that have a high direct effect and significant correlation to upland rice yield.